A network selection indicator based on golden relation between monetary cost and bandwidth in heterogeneous wireless networks - Salih Y.K.; See O.H.; Ibrahim R.W.; Yussof S.; Iqbal A. (Maxwell Science Publications, 2023)
The selection of an optimal access network is an essential aspect of service delivery in heterogeneous wireless networks. Many efficient methods are used in the selection of the best network. The relation between monetary cost and bandwidth affects the network selection process, but this consideration is not accounted for in other selection processes. This study proposes the use of golden ratio to determine the mathematical relation between monetary cost and bandwidth, which can serve as a viable indicator for both users and service providers. Results and analyses illustrate the efficiency of the suggested relation to select the best network in heterogeneous wireless networks and optimize user and network provider satisfaction levels. © Maxwell Scientific Organization, 2014.